Pengaruh ukuran perusahaan, leverage, komisaris independen dan kepemilikan manajerial terhadap integritas laporan keuangan - Fatin, Aisya Nisrina; Suzan, Leny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Financial reports are good when they are consistent, honestly prepared for what is happening within your organization, and contain credible information to make business decisions such as: ability to weigh the company's risk and return. Conservative proxies are used to assess the level of integrity in degrees. Conservative accounting carefully considers what you need to do to prepare for unforeseen circumstances in uncertain situations so that you do not overvalue assets or income or undervalue liabilities or expenses. This study aims to find out the impact of company size, leverage, independent commissioners, and managerial ownership on the integrity of financial statements, either simultaneously or partially, in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 research period. In conducting this research, the author uses a quantitative method with a population of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. Regression analysis of panel data was performed using Eviews 10 software. The results obtained show that the size of the company, leverage, independent agents, and management ownership at the same time affect the integrity of financial reporting. In part, the company's size undermines the integrity of the financial statements, but leverage, independent commissioners, and management ownership do not affect the integrity of the financial statements.